Pengembangan Tipologi Pesantren: Sebuah Kritik atas Tipologi Dhofier dan Ziemek - M. Holil; Asmuki Asmuki; Sokhibul Mighfar; Musyaffa Rafiqie (LP2M Universitas Ibrahimy, 2024)
The development of Islamic boarding schools is inevitable. Facts show that Islamic boarding schools have developed over time. The development referred to in this context is the development of the institutions within them. From what was initially only a kiai and a mosque, it continued to develop until there was a higher education institution. Throughout the history of the development of Islamic boarding schools, only two serious works have been found that map Islamic boarding schools into several types. The two figures are Zamakhsyari Dhofier and Manfred Ziemek. They have different opinions about the typology of Islamic boarding schools. The first mentions four typologies, while the second mentions five typologies of Islamic boarding schools. Ziemek seems to be dissatisfied with the typology of Islamic boarding schools proposed by Dhofier, so he developed it into five. This article was written in order to further develop the typology of Islamic boarding schools that they did. The development of this Islamic boarding school typology was carried out through a literature study by conducting a manuscript analysis, namely a comparison between one literature and another literature to support and reject the arguments built by the two figures. Through this literature analysis, it can be concluded that the typology of Islamic boarding schools can be developed into six types, namely types A-D remain, while the school and college indicators in Ziemek's type E version are separated, namely the college indicator is removed from type E and lowered to type F.